2014
DOI: 10.4028/www.scientific.net/msf.783-786.1171
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibrium between B2 Aluminide NiAl and Nb-Mo bcc Solid Solution Phase

Abstract: In order to understand the composition of the Nb-Mo bcc phase suitable to introduce B2-NiAl phase for the improvement of oxidation resistance as an Al reservoir layer for maintaining Al2O3 surface layer, a NiAl-Nb-Mo section of the quaternary Al-Nb-Ni-Mo phase diagram is studied. It is found that the ternary τ2 phase appears in wide composition range of alloys, both the hardness and cracking tendency decreases with increasing the Mo concentration of the alloys.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The atomic diameter of V, which is between that of NiAl-B2 and Nb, may be the reason why V substitutes for both sites in Nb(Ni,Al) 2 -C14. On the other hand, the reported Nb-Mo-NiAl isothermal section shows the preferential substitution of Mo on A-sites in Nb(Ni,Al) 2 -C14 16) because the diameter of Mo is larger than that of V. Similar relationships between the site occupancy behavior in the Ta(Ni,Al) 2 Laves phase and the diameters of additional elements (Cr, V and Mo) have been found in Ta-Cr-NiAl, Ta-V-NiAl, and Ta-Mo-NiAl isothermal sections. It can be concluded that the tendency of the site occupancy can be explained not only for ternary Laves phases but also for quaternary Laves phases that include Ni and Al, by taking the average atomic size of NiAl-B2 into account.…”
Section: Alloys Extrapolated Atomic Diameter Of Al [Nm]mentioning
confidence: 89%
See 1 more Smart Citation
“…The atomic diameter of V, which is between that of NiAl-B2 and Nb, may be the reason why V substitutes for both sites in Nb(Ni,Al) 2 -C14. On the other hand, the reported Nb-Mo-NiAl isothermal section shows the preferential substitution of Mo on A-sites in Nb(Ni,Al) 2 -C14 16) because the diameter of Mo is larger than that of V. Similar relationships between the site occupancy behavior in the Ta(Ni,Al) 2 Laves phase and the diameters of additional elements (Cr, V and Mo) have been found in Ta-Cr-NiAl, Ta-V-NiAl, and Ta-Mo-NiAl isothermal sections. It can be concluded that the tendency of the site occupancy can be explained not only for ternary Laves phases but also for quaternary Laves phases that include Ni and Al, by taking the average atomic size of NiAl-B2 into account.…”
Section: Alloys Extrapolated Atomic Diameter Of Al [Nm]mentioning
confidence: 89%
“…1). [13][14][15][16] It is suggested that Ta(Ni,Al) 2 -C14 and TaCr 2 seem to be a continuous solid solution in the Ta-Cr-NiAl system ( Fig. 1(a)), and in the sections of Ta-V-NiAl, the solubility of V in the Ta(Ni,Al) 2 Laves phase is quite large (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The coexistence relationships of Nb ss phase with PdAl(B2) phase in Nb-Pd-Al system [6] and also Mo ss (bcc ss ) phase with β-NiAl phase in Mo-Ni-Al system [7] have been reported. It is known that NiAl and has already reported phase equilibrium between B2-NiAl and (Nb,Mo)-bcc ss in the Nb-Mo-Ni-Al quaternary system with an atomic fraction of Mo in bcc ss of 0.59 or higher [9]. However, little information was found on the phase equilibrium in the Nb-Ni-Pd-Al quaternary system or quinary Nb-Mo-Ni-Pd-Al system and composition where bcc ss and B2 are in equilibrium is unknown.…”
Section: Introductionmentioning
confidence: 98%
“…Nb-Mo-NiAl-PdAl quasi-quaternary phase diagram at 1273 K (a) Nb-Mo-NiAl surface, (b) Nb-Mo-PdAl surface, (c) Nb-NiAl-PdAl surface. Solid lines are tie lines.Open marks in (a); S. Miura et al[9] CONCLUSIONS Bcc ss and B2 two-phase field in Nb-Mo-Ni-Pd-Al quinary system were described as the Nb-Mo-NiAl-PdAl quasi-quaternary phase diagram. Basic information of phase equilibrium between (Nb,Mo)-bcc ss substrates and (Ni,Pd)Al-B2 coatings are obtained and shown by plotting the values of Nb/(Nb+Mo) in bcc ss against Pd/(Pd+Ni) in B2.…”
mentioning
confidence: 98%